Stress reactivity and pain-mediated stress regulation in remitted patients with borderline personality disorder - Willis, Franziska; Kuniss, Sarah; Kleindienst, Nikolaus; Lis, Stefanie; Neukel, Corinne; Bohus, Martin; Treede, Rolf-Detlef; Baumgärtner, Ulf; Schmahl, Christian (Brain and behavior, 2018)
Objective: Patients with borderline personality disorder (BPD) use nonsuicidal self-injury (NSSI) to cope with states of elevated inner tension. It is unclear to what extent remitted BPD patients experience these states and whether the experience of pain still regulates emotion. The purpose of this study was the investigation of baseline stress levels, stress reactivity, and pain-mediated stress regulation in remitted BPD patients. Method: Subjective and objective stress parameters were assessed in 30 remitted BPD patients, 30 current BPD patients, and 30 healthy controls. After stress induction, a non-nociceptive tactile stimulus, a tissue-injuring, or a noninvasive pain stimulus was applied to the right volar forearm. Results Baseline stress levels of remitted BPD patients lie in between the stress levels of current BPD patients and healthy controls. Urge for NSSI increased significantly more in current than remitted BPD patients. The experience of pain led to a greater decrease of arousal in current compared to remitted BPD patients and healthy controls. Conclusions: States of increased tension still seem to appear in remitted BPD patients. The role of pain-mediated stress regulation appears to be reduced in remitted patients.